Desarrollo de un material de envase con propiedades antimicrobianas partiendo de residuos del plátano del mercado Mayorista del cantón Riobamba - Tuapanta Macas, Cristina Carolina (2025)
In light of the environmental impact caused by the massive use of fossil-based plastics for food packaging, it is imperative to develop new, more environmentally friendly alternatives such as active biodegradable films. In this context, the present research focused on obtaining an antimicrobial packaging material derived from banana residues sourced from the Wholesale Market of the Riobamba canton. For this purpose, cellulose was extracted from banana rachis through alkaline and bleaching processes and subsequently combined with polylactic acid (PLA) and ethyl lauroyl arginate (LAE) to produce the final material. Two concentrations of LAE were tested, 10% and 20%. The packaging materials were obtained using the solution-casting method. Structural properties were evaluated by Fourier-Transform Infrared Spectroscopy (FTIR-ATR), and antimicrobial activity against Escherichia coli and Staphylococcus aureus was assessed using the disk diffusion method. A two-factor experimental design was used to analyze the impact of the type of bacteria and the composition of the control substrate on antimicrobial activity. The results showed that the yield of the cellulose extraction process was 64%. FTIR-ATR analysis confirmed the effective extraction of cellulose and the incorporation of LAE into the films by identifying the functional groups associated with these compounds. Antimicrobial activity tests revealed that films containing 10% and 20% LAE inhibited the growth of E. coli and S. aureus, with inhibition halos ranging from 2.6 to 2.9 cm.